IPSC-induced podocytes from a BORS patient with EYA1 gene mutation showed glucocorticoid-resistant and cytoskeletal rearrangement - Guanyu Li; Di Lu; Liujing Xu; Shumin Zhou; Jiayi Zhang; Lijuan Wu; Lingna Shi; Lili Wang; Xiaoqing Lin; Zhigang Ma; Ming Liu; Xia Gao (Cellular and Molecular Life Sciences)
Abstract         The primary cause of branchio-oto-renal syndrome (BORS) is mutations in the EYA1 gene. The aim of this study was to investigate the clinical characteristics associated with induced podocyte reappearance in children with BORS and EYA1 mutations. We collected clinical and genetic data from a 4-year-old girl diagnosed with BORS and her family. Induced pluripotent stem cells (iPSC) were derived from peripheral blood mononuclear cells of both the patient and healthy individuals, which were differentiated into podocytes in vitro. RNA-seq was used to analyze differentially expressed genes in both groups. Here, the proband, along with his brother and mother, exhibited symptoms of BORS. WES analysis identified a heterozygous splicing variant at the EYA1 locus: c.1050 + 5G > A, inherited from his mother. The proband was initially glucocorticoid-resistant. After tacrolimus treatment, his urine protein/creatinine ratio significantly improved. Compared to healthy individuals, patient-derived podocytes displayed increased motility and pronounced cytoskeletal rearrangement. RNA-Seq results indicated significant downregulation of cell adhesion molecule and cytoskeletal rearrangement signaling pathway expression in patient-derived podocytes. Dexamethasone was ineffective in ameliorating the pathological damage induced by puromycin aminonucleoside in patient-derived podocytes. In BORS patients, podocytes exhibit cytoskeletal reorganization and enhanced motility in vitro while showing resistance to steroid treatment. These findings were consistent with the clinical features observed in the patient, suggesting that this unique cellular disease model merits further investigation.